Exploring the relationship between family income, food purchasing power, and nutritional adequacy in Babakan Village’s elementary school children - Ana Dina Resa; Putri Rahardianty Annisa (BIO Web of Conferences)
Adequate energy and protein is an important factor in supporting the growth of elementary school children. Inadequate nutritional intake can threaten physical and mental development, leading to poor academic performance. Economic factors (family income), play a significant role in determining a family's purchasing power. This study analysed the correlation between income, food purchasing power, and protein-energy intake adequacy in school-aged children near the IPB Dramaga Campus. This research used a cross-sectional design, where 39 children were purposively sampled. Data were collected through interviews with self- made questionnaires that have been validated. Most children came from low- income families (64.10%) and had severe deficits in energy and protein adequacy levels (41.03% and 46.15%). The correlation test showed no significant relationship between income and energy-protein adequacy level (p>0.05), but there was a significant relationship between income and purchasing power (p<0.05). The majority of subjects come from low-income families and experience severe energy and protein deficits. Income was not significantly correlated with energy-protein adequacy level but correlated considerably with purchasing power. Other factors, biases, and sample size should be considered in future research.